Pengaruh Kompetensi Dosen Terhadap Kepuasan Mahasiswa Di IAINU Kebumen - Ngasifatul Chasanah; Roikhanatul Fuadi; Ummu Fatin Khoriah; Umi Arifah (Tarbi: Jurnal Ilmiah Mahasiswa, 2026)
This study aims to determine the effect of lecturer competence on student satisfaction at IAINU Kebumen. Lecturer competence in this study encompasses four main dimensions: pedagogical, professional, personality, and social competence. This study used a quantitative method with a survey approach involving 54 students selected through a non-probability sampling technique. The research instrument used a Likert scale, which has been tested for validity and reliability. Data analysis was performed using simple linear regression. The results indicate that lecturer competence significantly influences student satisfaction, as indicated by a significance value of 0.000 < 0.05 and a regression coefficient of 0.614. The R-square value of 0.653 indicates that 65.3% of the variation in student satisfaction can be explained by lecturer competence. These findings confirm that lecturer quality, in terms of material mastery, teaching ability, personality, and social interaction, is a crucial factor in increasing student satisfaction. This study implies that continuous lecturer professional development is a strategic necessity for improving the quality of learning at IAINU Kebumen.